Literasi Media di Lingkungan Keluarga Dalam Mencegah Radikalisme Persepektif Al-Qur’an - Sodikin Sodikin (Assosiation of Islamic Education Lecturer of Universitas Jenderal Soedirman, 2019)
Media literacy such as Google, Facebook, Whatsapp, Twitter, Instagram, and Youtube, is currently growing rapidly in the family environment. The media worked not only as social media but also propaganda media. For the jihadists it is very efficient for propaganda in developing radicalism. This theme will be answered by the Quran, how is the view of the Quran regard to media literacy in the family environment in preventing radicalism. This research is a thematic study, this research puts forward library references (library reseach) in the field of interpretation of the Quran. Therefore, research materials were obtained from the Quran, Hadis, as well as books, articles and other works related to the object of research. The family is the smallest unit of community groups, consisting of father, mother and child. The conclusion of the research is that is in preventing radicalism in the family environment, both mothers, fathers, and all other family components play an important role in preventing radicalism, especially in filtering media usage, as stated in the QS. Luqman / 31: 13-19 and QS. al-‘Alaq / 96: 1-5.